محددات الهيكل المالي في المؤسسات البترولية الوطنية - دراسة تطبيقية لعينة من المؤسسات العاملة في منطقة حاسي مسعود للفترة) 2009-2014(- - بكاري, بالخير; قمو, سهيلة (جامعة الوادي - University of Eloued, 2017)
تهدف هذه الدراسة إلى التعرف على المحددات الأكثر تأثيرا في اختيار الهيكل المالي المناسب في المؤسسات البترولية الوطنية، حيث تمثلت المتغيرات المستقلة في الربحية، السيولة، معدل النمو، المردودية المالية، المردودية الاقتصادية، حجم المؤسسة، عمر المؤسسة، وهيكل الأصول ؛ أما المتغير التابع فيتمثل في الهيكل المالي المعبر عنه بنسبة الديون إلى الأموال الخاصة، وتشكلت عينة دراستنا هذه من ستة (06) مؤسسات بترولية وطنية متواجدة بمنطقة حاسي مسعود خلال الفترة-2009 2014 ؛ ولمعالجة هذا الموضوع فإننا اعتمدنا القوائم المالية لهذه المؤسسات وكذا برنامجي التحليل الإحصائي (data panel, spss) وبرنامج الجداول الإلكترونية. xlstat 2009 This study aimed to identify what are the determinants that influence the choice of An appropriate financial structure in the national petroleum firms, was where the independent variables in profitability, liquidity, growth rate, financial rentability, economic rentability, size of the firm, the age of the firm, and assets tangibility, and the variable It is to the financial structure. The sample was adopted in the study is six petroleum national firms located Hassi Messaoud area during the period 2009-2014, in order to address this issue we relied on the financial statements of these firms and programs for statistical analysis of data panel, spss and spreadsheet software Xlstat 2009.
مقال
Keywords: هيكل مالي، نسب مالية، هيكل رأس المال، أموال خاصة، استدانة، مردودية، حجم المؤسسة; Financial structure, financial ratios, capital structure, private funds, borrowing rentability, the size of the firm.